Determinación electroquímica de plumbemia en niños residentes en la Ciudad de Córdoba, Argentina - Wilke, Natalia (2000)
With the purpose of evaluating the incidence of environmental factors in the intoxication for lead in the infantile population, blood samples from 92 children which attended the Hospital Municipal Infantil of the City of Córdoba were studied. The lead concentration in blood was determined by means of an electrochemical technique "Potentiometric Stripping Analysis with Constant Current dissolution" (PSACC), appropriate for the determination of trace amounts of metallic cations in complex matrixes. In this work it has been used a static mercury drop electrode, which has allowed us to obtain reproducible results using a reduced volume of sample, smaller than 500 μL. The electroanalytical results were compared with those obtained by flame atomic absorption spectroscopy. Six patients (6,5%) presented high lead levels, above the limit imposed by the Centre of Disease Control of the United States (CDC) (10 μgDL-1). This result indicates that a high percentage of children is incorporating lead from their environments.